2013
DOI: 10.1007/s10103-013-1407-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diode laser (660 nm) on the rate of tooth movements: an animal study

Abstract: Low-level laser has been indicated to have the capability to facilitate the differentiation of the osteoclastic and osteoblastic cells which are responsible for the bone remodeling process. The aim of this study was to evaluate the effects of InGaAlP laser with a wavelength of 660 nm on the rate of tooth movement and histological status. Thirty male Wistar rats of 7 weeks old were selected for this study. The rats were randomly divided into two groups of 15 each to form the experimental (laser-irradiated) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
4
21
0
11
Order By: Relevance
“…Moreover, some animal studies have shown that laser diode irradiation can increase the amount of tooth movement (2-to 3-fold) in rats [18,19]. These results are consistent with other animal studies [7].…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, some animal studies have shown that laser diode irradiation can increase the amount of tooth movement (2-to 3-fold) in rats [18,19]. These results are consistent with other animal studies [7].…”
Section: Introductionsupporting
confidence: 82%
“…No presente trabalho foi empregada a microtomografia computadorizada in vivo para quantificar o deslocamento dentário, diferente dos estudos de A maioria das pesquisas, clínicas ou em animais experimentais, em ortodontia, que investigam o efeito da luz infravermelha durante a movimentação dentária, relacionam a aplicação do laser durante movimentação ortodôntica (Lim et al, 1995;Kawasaki;Shimizu, 2000;Cruz et al, 2004;Limpanichkul et al, 2006;Turhani et al, 2006;Seifi et al, 2007;Youssef et al, 2008;Fujita et al, 2008;Tortamano et al, 2009;Yoshida et al, 2009;Abi-Ramia et al, 2010;Habib et al, 2010;Gama et al, 2010;Marquezan et al, 2010;Yamaguchi et al, 2010;Sousa et al, 2011;Altan et al, 2012;Duan et al, 2012;Habib et al, 2012;Bicakci et al, 2012;Marquezan et al, 2013;Cossetin et al, 2013;Genc et al, 2013;Velásquez 2013;Kansal et al, 2014;Seifi et al, 2014;Hevari et al, 2014;Shirazi et al, 2015;Domínguez et al, 2015). O LED é pouco investigado como fonte de energia luminosa para verificar sua influência durante o movimento ortodôntico.…”
Section: Discussionunclassified
“…Assim, Shirazi et al(2015), com grupo experimental de 14 dias e coloração H&E, Altan et al(2012) Os efeitos do laser na polpa dentária, foi um aspecto reportado apenas por Abi-Ramia et al (2010); em seu estudo foram realizados cortes histológicos longitudinais e coloração H&E, e concluíram que a movimentação dentária induzida associada ao laser de baixa potência mostrou uma hiperemia reversível como uma resposta tecidual ao estímulo e que o laser permite um reparo mais rápido do tecido pulpar durante a movimentação ortodôntica.…”
Section: Movimentação Dentária Induzida E a Luz Infravermelha (Pesquiunclassified
See 2 more Smart Citations